First characterization of physicochemical and biological variables of the salt wetland dayat Morsli in Oran (Algeria). (December 2019) - Ben Bayer, Wided; Casse, Nathalie; Baba Hamed, Mohamed Bey; Denis, Françoise; Pasqualini, Vanina; Vaugoyeau, Marie; Caruso, Aurore
Abstract: Known to be on the outskirts of the city of Oran, 'dayat Morsli' is an endoreic wetland in western Algeria, and has suffered from many years of anthropogenic pollution (industrial and waste water). Dayat Morsli pool had never been characterized before, and the aim of this work is to understand the hydrological functions and the dynamic of this closed wetland, by monitoring biological, physical and chemical parameters for one year (2017). Water samples were collected monthly all around the lake. Measured parameters consisted of water level, pH, salinity, temperature, organic matter and phytoplankton abundance, in addition to the concentration of organic pollutants, nitrates and phosphates. The concentration of five heavy metals - cadmium, lead, iron, zinc and copper - was also determined. The results show that dayat Morsli is characterized as a salty to moderately salty wetland. The pH and salinity vary with the temperature and water level throughout the months. The phytoplankton cell concentration decreases with decreasing depth and increasing salinity. In parallel, during the second period of the year (June–December), organic matter accumulates and sediments out, while it decomposes during the first period. Moreover, nitrates and phosphates, essential elements for phytoplanktonic development, are found at concentrations above the standards with respective concentrations of 150 mg/L (NO3) and 6 mg/L (P), maybe causing the eutrophication of the wetland. We have shown that the average concentrations of Cd and Pb in water were higher than the allowed values. This study provides a better understanding of the functioning of dayat Morsli over one year, but also of the physicochemical and biological interactions in this small closed ecosystem. Moreover, these results could be used as a basis for the rehabilitation project of this wetland. Highlights: First characterization of dayat Morsli (Algerian lake). Two periods are observed: a period 1from January to May characterized by the water level, the cell count and the high pH, and a period 2 from June to december, characterized by changes in organic matter, temperature and salinity. A period is characterized by the variation of only three physicochemical and biological indicators. This wetland showed cadmium and lead pollution. Heavy metals evolved according to the physicochemical parameter changes.